Inter-annual trend of the primary contribution of ship emissions to PM2.5 concentrations in Venice (Italy): Efficiency of emissions mitigation strategies. (February 2015) - Contini, Daniele; Gambaro, Andrea; Donateo, Antonio; Cescon, Paolo; Cesari, Daniela; Merico, Eva; Belosi, Franco; Citron, Marta
Abstract: Ships and harbour emissions are currently increasing, due to the increase of tourism and trade, with potential impact on global air pollution and climate. At local scale, in-port ship emissions influence air quality in coastal areas impacting on health of coastal communities. International legislations to reduce ship emissions, both at Worldwide and European levels, are mainly based on the use of low-sulphur content fuel. In this work an analysis of the inter-annual trends of primary contribution, ε, of tourist shipping to the atmospheric PM2.5 concentrations in the urban area of Venice has been performed. Measurements have been taken in the summer periods of 2007, 2009 and 2012. Results show a decrease of ε from 7% (±1%) in 2007 to 5% (±1%) in 2009 and to 3.5% (±1%) in 2012. The meteorological and micrometeorological conditions of the campaigns were similar. Tourist ship traffic during measurement campaigns increased, in terms of gross tonnage, of about 25.4% from 2007 to 2009 and of 17.6% from 2009 to 2012. The decrease of ε was associated to the effect of a voluntary agreement (Venice Blue Flag) for the use of low-sulphur content fuel enforced in the area between 2007 and 2009 and to the implementation of the 2005/33/CE Directive in 2010. Results show that the use of low-sulphur fuel could effectively reduce the impact of shipping to atmospheric primary particles at local scale. Further, voluntary agreement could also be effective in reducing the impact of shipping on local air quality in coastal areas. Highlights: Primary contributions of ship traffic emissions to PM2.5 and PNC were evaluated. Contribution to particle number concentration is two times lager than that to PM2.5 . Contribution to PM2.5 reduced by 50% from 2007 to 2012 while ship traffic increased. The use of low-sulphur fuel reduces primary contribution of ships to PM2.5 . Use of cleaner fuels reduces impact of ships traffic on local air quality.